Thinking goes to school : Piaget's theory in practice - Furth, Hans G.; Wachs, Harry (Oxford University Press, 1975)
Proposes to show how children can be prepared to develop their full potential as 'thinking' human beings. The activities or 'games' described provide a general foundation which should help the child to deal successfully with specific academic subjects. With Additional Thoughts.